The impact of culture on money attitudes: understanding honor, face, and dignity and their relation to money scripts - Sholin, Travis (Kansas State University, 2022)
Cultural awareness in financial planning is of increasing importance as the world’s cultures continue to blend. This dissertation aims to distinguish three types of culture: honor, face, and dignity (HFD) (Leung & Cohen, 2011). Utilizing prior research to validate the HFD distinctions for the individuals surveyed, this research explored cultural correlations with money scripts (Klontz & Britt, 2012). Data was collected from 750 participants within targeted regions and demographics using Amazon Mechanical Turk (MTurk). Honor, face, and dignity, used for the independent variables, were each analyzed using scales similar to those from Yao et al. (2017). An exploratory factor analysis and a confirmatory factor analysis were used to validate the HFD scales. HFD were important pieces to the cultural component of this research. It extends cross-cultural research beyond traditional east-west/individualistic-collectivistic comparisons and breaks east/collectivist cultures into honor and face. It offers a more comprehensive cultural lens that we aspire to use to look at different money attitudes. The money attitudes, used for the dependent variables, were each analyzed using the KMSI-R questions and scales developed by Taylor et al. (2015). The four money attitudes are money avoidance, money status, money worship, and money vigilance. An exploratory factor analysis and a confirmatory factor analysis were used to validate the four scales. Understanding the relationship between different cultures and their money attitudes was important for this study as it aims to observe the relationships between culture and financial planning/financial psychology. Ordinary Least Squares regression analyses were run to analyze the various relationships. Results from this study reveal that there are statistically significant relationships between HFD and money avoidance, money worship, and money vigilance. For money status, honor and dignity had statistically significant relationships. These findings are an addition to cross-cultural financial planning and financial psychology literature. This exploratory research should be of interest to financial planners, financial psychologists, financial therapists, and behavioral scientists.
Keywords: Cross-culture; Honor; Face; Dignity; Money scripts